Analysis of the temperature distribution in the pin bundle of the CIRCE facility. (November 2020) - Buzzi, F.; Pucciarelli, A.; Galleni, F.; Tarantino, M.; Forgione, N.
Highlights: CFD calculations of LBE Thermal-Hydraulics in a fuel pin simulator (FPS) were performed. Numerical temperature trends were compared with measurements for transient and steady-state conditions. The influence of the spacer grids on the temperature and velocity fields were investigated. The heat exchange between the external pool and the FPS can not be neglected in the transient calculations. Abstract: In this paper, a CFD analysis of the Fuel Pin Simulator (FPS) of the CIRCE-HERO facility built at the ENEA research centre in Brasimone was performed. STAR-CCM + code was used with the purpose of reproducing steady-state and transient experimental conditions adopting LBE as working fluid. RANS and URANS simulations were performed comparing the calculated temperature trends with the experimental data. In particular, the FPS average outlet temperature was monitored for the transient case and an exhaustive study of the heat transfer between the FPS and the pool during the transient was carried out. The impact of the involved heat transfer phenomena on the FPS energy balance was studied from a quantitative point of view and the relevant difference in terms of thermal inertia between pool and FPS component was pointed out.